Design and implementation of a supplier kanban system - Lyra, Raquel Beatriz Gonçalves Ralha Trindade (2022)
This project was developed with the company Gestamp Palau S.A. The purpose of the project was to design a non-electronic consignation supplier Kanban System in a high variability context. This project resulted from the company's request to change its current child parts supply system from a logic needs planning push system to a Kanban consignment system. To achieve this, we conducted four Action Research cycles. Three of these culminated in the development of a Kanban solution. All the solutions developed used the Kanban formula proposed by Toyota. However, each solution used a different tactic to determine safety stock and/or demand. Of the three solutions developed, the last one was considered to be the best for the specific conditions of this case. In this final solution the number of kanbans was defined considering that the demand in the Kanban formula was equal to the machine’s maximum consumption - an oversized system. To make it possible to store the number of kanbans in the area available it was necessary to establish a supplier frequency of two days. Considering that the Kanban was oversized stockouts are expected to be avoided. Additionally, the fact that the supply of the child part components will no longer use carton boxes allowed to: 1) attain the company’s objective of reducing plastic and carton in the plant; 2) eliminate the operator’s supermarket task of transferring some references to KLTs; and 3) standardize the packages in the supermarket (small components in KLTs).